Tales of tails: Sales distribution and the role of retail channels in the German book market - Daniel Lüke (Philipps-University Marburg, School of Business and Economics, 2024)
This paper examines the sales distribution and genre composition of the German book market across different retail channels - e-commerce, chain stores, and independent bookstores - over the period 2011-2018. Utilizing a unique dataset comprising weekly sales data of approximately 50,000 top-selling book titles, the study challenges the economic relevance of the "long tail" effect, which suggests that niche products hold significant market share due to digitalization. Our findings reveal that both online and offline sales are heavily concentrated on a few best-selling titles, with the "long tail" products accounting for a negligible proportion of overall sales. However, a "middle tail" of moderately popular books, more prominent in online sales and independent bookstores, suggests diverse consumption patterns not captured by conventional models focusing on the extremes of sales distributions. We further observe significant differences in the genre composition and attributes of books sold across channels, filling a gap in the existing literature. For example, chain stores exhibit higher concentrations of bestsellers, while independent bookstores show a more diverse array of less recent titles. These findings imply that consumer preferences vary significantly by retail channel, indicating limited substitutability between channels.
Keywords: L81; L82; Z11; 330; Buch; Markt; Absatz; Statistische Verteilung; Einzelhandel; Handelskette; Electronic Commerce; Deutschland